Penjadwalan Dinamis Menggunakan Metode Rolling Time Window (RTW) pada Kasus Flowshop 3 Mesin untuk Meminimumkan Total Biaya Lateness, Earliness dan Re-Scheduling - Yusriski, Rinto; Budi Astuti; Andri Rachmat Kumalasian Nasution (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2023)
This study discusses the problem of job scheduling in a three-machine flowshop to minimize the total cost of lateness, earliness, and rescheduling. This research takes a real system from one of the manufacturing companies engaged in the machining operations of various components. There are 12 jobs with different arrival patterns and due dates. The company uses the first-in, first-out (FIFO) scheduling method and gets the result that some products finish early and some finish late. This study tries to improve the company's scheduling performance by proposing a rescheduling using the rolling time window (RTW) method. Although it is relatively small, scheduling results show an improvement in company performance as measured by the total cost of earliness, lateness, and rescheduling, although it is relatively small (3%). This improvement is obtained by suggesting the company reschedule every 15 days by evaluating the length of the window per 30 days. The company can still use the FIFO method used by the company considering the characteristics of the jobs that come to it are still under control. The company is deemed capable of making agreements with consumers regarding the delivery deadline, making the job queues on the production floor less crowded.